Annual Report 1988-89 Government of India Planning Commission - Planning Commission (Planning Commission, 1988)
1988-89 has been a very good year. The economy has shown excellent recovery in agricultural production and sustained the momentum of industrial growth. It is visualised that the Gross Domestic Product will show a growth rate of over 9 per cent for the year. 1.2 This performance has to be seen in the context of severe drought in the preceding year. These two years have demonstrated certain inherent strengths of the economy. The first is the resilience of the system in the face of severe weather aberrations and the second is the sustained growth performance in the sphere of industry and infrastructure.
Government of India Planning Commission